a) Sievennä a^2/3-(-a/3)^2

b) Ratkaise epäyhtälö (x-3)^2>(x-1)*(x+1)

c) Määritä suorien x/3+y/2=1 ja 3x-2y+3=0 leikkauspiste.

a) (-a/3)^2=(-a/3)*(-a/3)=a^2/9

a^2/3-a^2/9=(3*a^2)/9-a^2/9=(2*a^2)/9

Vastaus: (2*a^2)/9

b) (x-3)^2=x^2-3x-3x+9

(x-1)*(x+1)=x^2+x-x-1=x^2-1

x^2-3x-3x+9>x^2-1

-6x>-10

x<-10/-6

x<1 2/3

Vastaus: x>5/3

c) x/3+y/2=1

y/2=1-x/3

y=(1-x/3)*2

y=-2x/3+2

3x-2y+3=0

-2y=-3x-3

y=3/2x+3/2

-(2*x-6)/3=(3*x+3)/2

x=3/13

y=-(2*(3/13)-6)/3 tai y=(3*(3/13)+3)/2

y=24/13

x=3/13 y=24/13

(3/13)/3+(24/13)/2=1

3*(3/13)-2*(24/13)+3=0

Vastaus: x=3/13 y=24/13